O fenômeno da precarização laboral: uma investigação sobre as professoras da rede pública de ensino do município de Fortaleza - Souza, Karlinne de Oliveira (2015)
This research is linked to the Graduation Program in Psychology of the Federal University of Ceará and aims at analyzing the process of labor precarization experienced by the teachers of the municipal educational network. For this propose, the research intends to describe the labor conditions referred to these professionals and also to identify the characteristics and evidences of precarization in their teaching activities. The theoretical basis that supports our research relies on the thoughts of authors such as Agulló, 2001; Bilbao, 1999; Castel, 2008; Antunes, 1998; Aquino, 2005; Alonso, 2000, which point out to a new configuration of the labor reality and describe a scenario filled with changes in the employment schemes, intensification of work and acceleration of times, as well as weakening of the social cohesion granted by work. Such scenario composes what we call labor precarization. The transformations that occurred in the labor world are present-day and also interfere in the educational context. We understand that women, young people, elderly and immigrants are the social groups that are affected the most by precarization. Based on this observation, we chose to investigate one of these groups, namely, women. The research has a qualitative intent. Regarding the data construction, we made use of observation and semi-structured interviews. The data analysis procedure, guided by the content analysis technique proposed by Bardin (2008), allowed us to identify the process of precarization through the perspective of work intensification. We built our analysis categories from the following thematic blocks: the complexity of school performance demand, the family cooperation and the social issue, the Inclusive Education, and the conditions and organization of work. We discussed these themes, focusing on how the process of labor precarization, here represented by the intensification of work, is understood with respect to these categories. The study also discusses the consequences for teachers, such as suffering and the ongoing risk of disease.